Service dogs for autistic children and family system functioning: a constant comparative analysis - Leighton, Sarah C.; Rodriguez, Kerri E.; Nieforth, Leanne O.; O’Haire, Marguerite E. (Frontiers in Psychiatry, 2023)
Service dog placements for autistic children are growing in popularity, yet findings to date are mixed. Moreover, no study to date has examined these placements through the lens of a recognized theoretical model. The purpose of this study is twofold: to explore experiences reported by caretakers of autistic children involved in a service dog program, and to contextualize findings within an established theoretical framework. A total of N = 50 caretakers of autistic children (n = 38 with and n = 12 without a service dog) were recruited through the national non-profit service dog provider Canine Companions. Participants completed an online survey through Qualtrics which asked open-ended questions about their experiences, both negative and positive. Constant comparative analysis identified two high level themes, nested within a family systems approach framework: 1) Enhancing social functioning of the family system unit, and 2) Fostering stability and strength within family system subunits. These themes interacted holistically to foster and reinforce family system resilience. Placements led to greater social inclusion for children and their families, acted as a highly individualized intervention, and decreased experiences of judgement and stigma. Perceived as members of the family, service dogs may co-regulate with the autistic child and family members and can be a source of joyful connection within the family. Results highlighted the service dog’s influence on the entire family (beyond the autistic child). Implications for service dog organizations suggest it may be helpful to account for family-wide impacts throughout the placement process. High standards on the part of provider organizations may minimize negatives, optimizing outcomes for both humans and canines. Ultimately, findings enrich our understanding of service dog interventions for autistic children.